(untitled) ([Bohol, Philippines], 2003)
The three volumes series are the results of a partner's identified and managed three year capability building programme on community - based Coastal Resource Management that began in 1996. The capability buiding programme evolved from OGB and its partners collectively identifying prioritising and committing to build their capacities on the following themes or areas of concern to make their respective CBCRM progammes effective.
Keywords: Coastal zone management,Fishery management,Quản lý vùng ven biển,Quản lý nghề cá; Citizen participation,Tham gia của cộng đồng